1999
DOI: 10.1161/01.cir.99.21.2717
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin Promoter 5A/6A Polymorphism Is Associated With Acute Myocardial Infarction

Abstract: The 5A/6A polymorphism in the promoter of the stromelysin gene is a novel pathogenetic risk factor for AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 9 publications
4
90
2
4
Order By: Relevance
“…Three functional polymorphisms of MMPs are known to be related to coronary artery disease, i.e., MMP-3, MMP-9, and MMP-12 (Ye et al 1995;Terashima et al 1999;Zhang et al 1999;Jormsjo et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Three functional polymorphisms of MMPs are known to be related to coronary artery disease, i.e., MMP-3, MMP-9, and MMP-12 (Ye et al 1995;Terashima et al 1999;Zhang et al 1999;Jormsjo et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Association of 5A allele with MI were reported in Japanese populations (14,15), in young (45 years) Han-Chinese patients from Taiwan (16), in Han-Chinese patients from China (17) and in Caucasians (18). However a genome wide association study looking at 112 polymorphisms in 71 candidate genes in 4152 Japanese people found an association between the 6A allele and MI, although this was confined to women (19).…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms have been studied in several diseases including ovarian and colorectal cancer, myocardial infarction, aortic aneurysm and coronary atherosclerosis [19]. The MMP-3 5A/6A polymorphism, which has either five or six consecutive adenosine bases, has been associated with high blood pressure [21], acute myocardial infarction [22], aortic stiffening [23] and has been shown as independent predictor of cardiac mortality in patients with non-ischaemic cardiomyopathy [24]. In the present study, we investigated whether polymorphic variations in the promoter of MMP-1 and MMP-3 genes predict the adaptive response to mitral regurgitation in patients with MVP.…”
Section: Discussionmentioning
confidence: 99%